Labor Relations Law in the Public Sector and the Fourth Rule of the Protective Principle - Ubilla Fernández, Gonzalo (Universidad Hemisferios, 2021)
This paper focuses on developing the issue of labor relations in the public sector, and more specifically in the area of the protective nature that the Uruguayan legal system displays on the functional link between the State as employer and the public official as worker. The approach to be taken on the subject will be based on a vision of the general principles of Labor Law, and a constructive syllogistic position in a tertium genus view between Labor Law and Administrative Law for the phenomenon of labor relations in the public sector. On the basis of this idea of common formation and construction among both branches of Law, an attempt will be made to propose the figure of a fourth rule in the form of action of Labor Law operates. Analyzing the impact and scope of the presence of this new legal concept with the aim of protecting public officials and providing a new distinctive element to continue thinking about whether or not we are dealing with a new autonomous branch of Law.